Strategic management and business policy globalization, innovation, and sustainability - Wheelen, Thomas L.; Hunger, J. David 1941-; Hoffman, Alan N. (Alan Nathan) 1954-; Bamford, Charles E. (Pearson, 2015)
This text equips readers with the strategic concepts they will need to know as we face issues such as climate change, global warming and energy availability.